Tata Kelola Kolaboratif Antara Pemerintah Daerah, Sekolah, dan Komunitas dalam Meningkatkan Kualitas Pendidikan Dasar di Kabupaten Sidoarjo - Rahma Tirtaningrum; Ulul Albab; Kristyan Dwijosusilo (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to explore collaborative management between local governments, educational institutions, and communities in improving the quality of basic education in Sidoarjo Regency. The background of this research stems from the increasing need for an adaptive, participatory, and sustainable education system in the era of decentralization, where intersectoral collaboration is key to realizing quality and equitable education. Sidoarjo Regency, as a region with rapid economic and social growth, faces obstacles in the distribution of quality basic education, particularly related to community participation, policy collaboration, and human resource capacity building at the school level. This study applies a qualitative approach through a case study method, involving resource persons from the Sidoarjo Regency Education Office, principals, teachers, school committees, and the education community. Data collection was conducted through in-depth interviews, participant observation, and analysis of regional education policy documents. Research findings indicate that collaboration between various actors has successfully improved education quality through community-based learning mentoring programs, teacher training, and innovative policies in school management. However, the implementation of collaboration continues to face obstacles such as lack of coordination between agencies, budget constraints, and ineffective joint program evaluation. The study concludes that successful collaborative management requires shared commitment, transparent communication, and ongoing policy support. Research recommendations emphasize the importance of enhancing intersectoral collaboration capacity, local education dialogue forums, and performance-based evaluation systems to maintain the sustainability of basic education quality in Sidoarjo Regency.